2002
DOI: 10.1002/j.1551-8833.2002.tb09477.x
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Effect of Trace Element Contaminants in Alum

Abstract: Analytical methods were developed to accurately determine the levels of the most prevalent trace metal contaminants in a variety of alum feedstocks used in the coagulation process of drinking water treatment. A combination of chelation ion chromatography, chelation extraction–atomic absorption spectrometry, and hydride generation atomic fluorescence allowed for the selective isolation of trace metals from the alum matrix with a high degree of precision and sensitivity. Trace levels of arsenic, cadmium, chromiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Despite this, some studies have suggested that recycled coagulant does have a detrimental impact on treated water quality with respect to color in treated water when dosed at 3.9 mg/L Al (Eyring et al, 2002) Unselectively recovered alum worst-case potential conc. in treated water when dosed at 26 mg/L Al (Bishop et al, 1987) Selectively recovered alum diluted when dosed at 3.9 mg/L recovered Al ( Recovered with 20% extra dose of fresh alum * Recovered (81% of total) 0 3.2 (11.5) 3.2 (11.5) Fresh 3.9 0.7 1.5 Total 3.9 3.9 (11.5) 4.7 (11.5) * A hypothetical extra dose of coagulant to compensate for removal of organic contaminants carried over in recovered coagulant.…”
Section: Recovered Coagulant Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, some studies have suggested that recycled coagulant does have a detrimental impact on treated water quality with respect to color in treated water when dosed at 3.9 mg/L Al (Eyring et al, 2002) Unselectively recovered alum worst-case potential conc. in treated water when dosed at 26 mg/L Al (Bishop et al, 1987) Selectively recovered alum diluted when dosed at 3.9 mg/L recovered Al ( Recovered with 20% extra dose of fresh alum * Recovered (81% of total) 0 3.2 (11.5) 3.2 (11.5) Fresh 3.9 0.7 1.5 Total 3.9 3.9 (11.5) 4.7 (11.5) * A hypothetical extra dose of coagulant to compensate for removal of organic contaminants carried over in recovered coagulant.…”
Section: Recovered Coagulant Qualitymentioning
confidence: 99%
“…in treated water when dosed at 26 mg/L Al (Bishop et al, 1987) Selectively recovered alum diluted when dosed at 3.9 mg/L recovered Al ( Recovered with 20% extra dose of fresh alum * Recovered (81% of total) 0 3.2 (11.5) 3.2 (11.5) Fresh 3.9 0.7 1.5 Total 3.9 3.9 (11.5) 4.7 (11.5) * A hypothetical extra dose of coagulant to compensate for removal of organic contaminants carried over in recovered coagulant. Doses and recovery yield adapted from Eyring et al (2002); and Prakash and Sengupta (2004). (Lindsey and Tongkasame, 1975), although reported increases in trihalomethane formation potential (TTHMFP) have been small (Bishop et al, 1987).…”
Section: Recovered Coagulant Qualitymentioning
confidence: 99%
“…Cr may also be a trace contaminant in treatment chemicals. For example, Eyring et al (2002) measured Cr in alum coagulants, potentially yielding 0.24 µg/L Cr in water at commonly applied alum doses. More recently, a water treatment plant in Missouri found that Cr(VI) increased from 0.1 µg/L in the raw water to 0.6 µg/L at the end of the treatment plant (MDNR, 2010), with the suspected source being the plant's alum and/or lime.…”
Section: Engineering Considerations For Cr Treatmentmentioning
confidence: 99%
“…One important advantage of using this technique is that low dilution factors (1:4) are suitable. A second major advantage of ICP–OES versus other methods is that multiple metals (up to 28 in this study) can be analyzed in a single run (compare 12 metals analyzed using five separate analytical methods, as outlined in Eyring et al, 2002). Before aspiration into the ICP–OES apparatus, the treatment‐chemical samples were diluted with distilled water and acidified with reagent‐grade hydrochloric acid.…”
Section: Measurement Of Treatment‐chemical Compositions and Their Effmentioning
confidence: 99%
“…The most recent data available in the literature on the trace metal composition of alum products were reported by Eyring et al (2002). These alum products were not identified, but they are characteristic of low‐iron alum.…”
Section: Measurement Of Treatment‐chemical Compositions and Their Effmentioning
confidence: 99%